Differential cellular uptake and metabolism of curcuminoids in monocytes/macrophages: regulatory effects on lipid accumulation - Nakagawa, Kiyotaka; Zingg, Jean-Marc; Kim, Sharon H.; Thomas, Michael J.; Dolnikowski, Gregory G.; Azzi, Angelo; Miyazawa, Teruo; Meydani, Mohsen (British journal of nutrition, 2014)
We have previously shown that curcumin (CUR) may increase lipid accumulation in cultured human acute monocytic leukaemia cell line THP-1 monocytes/macrophages, but that tetrahydrocurcumin (THC), an in vivo metabolite of CUR, has no such effect. In the present study, we hypothesised that the different cellular uptake and/or metabolism of CUR and THC might be a possible explanation for the previously observed differences in their effects on lipid accumulation in THP-1 monocytes/macrophages. Chromatography with tandem MS revealed that CUR was readily taken up by THP-1 monocytes/macrophages and slowly metabolised to hexahydrocurcumin sulphate. By contrast, the uptake of THC was low. In parallel with CUR uptake, increased lipid uptake was observed in THP-1 macrophages but not with the uptake of THC or another CUR metabolite and structurally related compounds. From these results, it is possible to deduce that CUR and THC are taken up and metabolised differently in THP-1 cells, which determine their biological activity. The remarkable differential cellular uptake of CUR, relative to THC and other similar molecules, may imply that the CUR uptake into cells may occur via a transporter.